Faktor Penyebab Terjadinya Peningkatan Pelanggaran Lalu Lintas Di Wilayah Hukum Polresta Jambi - Aidi, Khasnatul; Irwan; Sariani, Dona (Civic Education Perspective Journal, 2023)
The purpose of this research is to find out the factors that cause an increase in traffic violations in the jurisdiction of Polresta Jambi. Data collection This research was conducted at the Polresta Jambi and research was conducted in the Jambi City area from 5 December 2022 to 15 February 2023. The method for collecting data used observation, interview and documentation techniques. The data analysis used is qualitative in nature. The results obtained after the implementation of the research The factors causing the increase in traffic violations in the jurisdiction of the Jambi Police are due to human factors, vehicle factors, and road factors. Human factors are the most numerous or dominant traffic violations compared to other factors. Traffic violations due to the human factor in Jambi City are caused by various reasons including: wanting to save time and money, being careless, in a hurry, wanting to get to your destination quickly, and being forgetful or negligent. The most common types of violations committed related to human factors that occurred in Jambi City include: violations related to the number of passengers, violations related to the use of helmets, violations related to not being able to show STNK and SIM, and violations related to running red lights.